Nucleolar coefficient and cytochemistry of human blood monocytes - Smetana, K; Chan, P K; Jirásková, I; Busch, H (Life sciences, 1997)
Nucleoli in peripheral blood monocytes represented mostly by micronucleoli were investigated by means of cytochemical procedures for the demonstration of RNA, proteins of silver stained nucleolus organizer region, nucleophosmin, nucleolin and fibrillarin. The values of the nucleolar coefficient (mean number of nucleoli per cell) were influenced by the procedure used for the visualization of nucleoli. The differences in the values of the nucleolar coefficient of monocytes in one and the same person using above mentioned procedures suggested that micronucleoli in blood monocytes represent heterogeneous nuclear structures and only some of them possess both RNA and characteristic nucleolar proteins. Therefore, the procedures used for the visualization of nucleoli must be always taken into consideration when the values of the nucleolar coefficient are evaluated.
Keywords: Cell Nucleolus; Male; Nucleolin; monocyty; Chromosomal Proteins, Non-Histone; fosfoproteiny; proteiny vázající RNA; ribonukleoproteiny; Humans; Nucleophosmin; nukleolin; chromozomální proteiny, nehistonové; mužské pohlaví; RNA; organizátor jadérka; RNA-Binding Proteins; Phosphoproteins; Monocytes; Adult; buněčné jadérko; nukleofosmin; jaderné proteiny; Nuclear Proteins; Ribonucleoproteins; Nucleolus Organizer Region; dospělí; lidé